2021
DOI: 10.1016/j.celrep.2021.109746
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed functional metagenomic analysis of the infant microbiome identifies effectors of NF-κB, autophagy, and cellular redox state

Abstract: Summary The human microbiota plays a critical role in host health. Proper development of the infant microbiome is particularly important. Its dysbiosis leads to both short-term health issues and long-term disorders lasting into adulthood. A central way in which the microbiome interacts with the host is through the production of effector molecules, such as proteins and small molecules. Here, a metagenomic library constructed from 14 infant stool microbiomes is analyzed for the production of effectors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…8 Commendamide ( N -acyl-3-hydroxypalmitoyl)-glycine ( 7 ), a metabolite produced by Bacteroides vulgatus , was shown to activate G protein-coupled receptors (GPCRs). 9 Regarding NRPS-derived natural products, a sequence analysis of gut NRPSs in the human microbiome uncovered two new compounds, humimycin A ( 8 ) and humimycin B ( 9 ), which have been shown to be inhibitors of lipid II flippase (MurJ) against Staphylococcus aureus . 10 These are also good leading compounds for the development of anti-infection drugs.…”
Section: Gut Microbiota-derived and Biologically Active Npsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Commendamide ( N -acyl-3-hydroxypalmitoyl)-glycine ( 7 ), a metabolite produced by Bacteroides vulgatus , was shown to activate G protein-coupled receptors (GPCRs). 9 Regarding NRPS-derived natural products, a sequence analysis of gut NRPSs in the human microbiome uncovered two new compounds, humimycin A ( 8 ) and humimycin B ( 9 ), which have been shown to be inhibitors of lipid II flippase (MurJ) against Staphylococcus aureus . 10 These are also good leading compounds for the development of anti-infection drugs.…”
Section: Gut Microbiota-derived and Biologically Active Npsmentioning
confidence: 99%
“…7,53 Functional (meta)genomics mining approach led to the discovery of the GPCR agonist commendamide and N -acyl serinol. 9 A deep learning approach based on multiple natural language processing (NLP) neural network models was developed to mine antimicrobial peptides from the human gut microbiome. 18,53 The further development of suitable hosts for heterologous expression, new gene editing tools, and gene modulation tools are crucial for increasing the speed of identification of gut microbiota-derived NPs.…”
Section: Gut Microbiota-derived and Biologically Active Npsmentioning
confidence: 99%
“…In a very inspiring study ( Cohen et al, 2015 ), Cohen et al showed that commendamide was indeed able to interact with GPCRs by acting as an agonist of the GPCR G2A/132 receptor, implicated in autoimmunity and atherosclerosis. These interesting structural properties, its biogenic origin and bioactivity ( Cohen et al, 2015 ; Lynch et al, 2017 ; Lynch et al, 2019 ; Piscotta et al, 2021 ), but also the presence of an N -(3-hydroxyacyl)amino acid scaffold, which is a structural motif found in many other interesting bioactive products ( Morishita et al, 1997 ; Nemoto et al, 1998 ; Fuqua and Greenberg, 2002 ; Grandclément et al, 2016 ; Lynch et al, 2019 ), make of commendamide, a metabolite at the cross-road of gut microbiota and host signaling, an exceptionally attractive target for chemical synthesis.…”
Section: Introductionmentioning
confidence: 99%